Terrestrial Isopoda (Crustacea, Oniscidea) from the coasts of Costa Rica, with descriptions of three new species - Taiti, Stefano (2018)
Abstract: Seven species of terrestrial isopods are recorded from the coasts of the Pacific and Caribbean sides of Costa Rica. Three species (Buchnerillo neotropicalis, Hawaiioscia nicoyaensis and Trichorhina biocellata) are described as new and two species (Tylos niveus and Armadilloniscus cf. caraibicus) are newly recorded from the country. The poorly known species T. niveus is also illustrated. At present the total number of terrestrial isopod species recorded from Costa Rica is 30. Interestingly four typical littoral halophilic species (Ligia baudiniana, Tylos wegeneri, T. niveus and A. cf. caraibicus) are present on both the Pacific coast of Costa Rica and on the coasts of the lands encompassed by the Caribbean Sea. With the sole exception of A. cf. caraibicus, no morphological differences could be detected from the Pacific and Caribbean populations of those species. Rev. Biol. Trop. 66(Suppl. 1): S187-S210. Epub 2018 April 01.